Cement modified and copper oxide enriched ferric sludge as oxygen carrier for chemical looping combustion - Koh Yang, Chat How Joewin (2024)
This study focuses on enhancing the performance of water treatment sludge as an oxygen carrier (OC) for chemical looping combustion (CLC) of municipal solid waste (MSW) syngas. High aluminate cement was introduced to augment the OC's mechanical strength, concurrently preventing inter-particulate agglomeration, resulting in a commendable and low agglomeration rate of 3.44% after 50 cycles. The inclusion of CuO proves to be instrumental in boosting the OC's reactivity, mitigating the loss of active components due to the addition of cement support. Notably, FSCuO10 (Ferric sludge with 10% CuO addition) demonstrates over 92% CO efficiency throughout 50 cycles, affirming the success of the dual modification of FS. The investigation also delves into comprehending the reduction process, agglomeration pathways, and the impact of varied CuO percentages has on OC performance. Extensive characterizations were conducted to elucidate OC transformations and their consequential effects on reactivity, physical characteristics, and overall performance. A noteworthy observation includes the outward migration of iron and copper during CLC, contributing to the stabilization of reactivity. In summary, the modifications implemented on FS, yield an improved OC for CLC purposes, maintaining its novelty and cost-effectiveness. The novelty stems from the interactions between CuO and FS, leading to improved reactivity and stability, as well as the extended CLC, which demonstrates the longevity of the OCs. This research contributes to the circularity of waste-derived products by effectively repurposing water treatment sludge and improving sustainable waste management practices.